Vagal nerve schwannoma: a rare case from Border Security Force Composite hospital - Bhattacharya, Kaushik; Sarkar, Somi Dey; Biswas, Tapan (International Surgery Journal, 2018)
Cervical vagal schwannoma is an extremely rare entity, slow growing, solitary, asymptomatic benign neck mass associated with vagus nerve. Definitive pre-operative diagnosis may be difficult and investigations such as fine needle aspiration biopsy (FNAB) have low specificity. Surgical excision is the treatment of choice. We describe a 26-year-old female presenting as right neck mass who underwent surgery. Magnetic resonance imaging was done, and patient was operated under general anaesthesia. Intraoperatively, the tumour was found to be originating from the vagus nerve. Final histopathology confirmed our preoperative suspicion of vagal nerve schwannoma. Vagus nerve schwannomas should be distinguished from other tumours that arise in the neck before planning surgery, to minimize the risk of nerve injury. A careful surgical technique is mandatory for tumour clearance and to reduce postoperative complications.